2023
DOI: 10.1002/adom.202301110
|View full text |Cite
|
Sign up to set email alerts
|

Turning Self‐Trapped Exciton Emission to Near‐Infrared Region in Thermochromism Zero‐Dimensional Hybrid Metal Halides

Abstract: Low dimensional lead‐free metal halides have become the spotlight of the research on developing multifunctional optoelectronic materials as their properties show a wide range of tunability. However, most reported low dimensional metal halides only function in the ultra‐violet to visible range due to their large bandgap. Moreover, the organic cation based low dimensional metal halides show limited thermal stability; on the other hand, their inorganic cation based counterparts suffer from limited solution proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The broadband emission from TJU-41 and TJU-42 is highly stable over the chemical treatments in aqueous conditions (pH = 3–11) as well as polar organic solvents (Figure f,g). After incubation in these solutions for 48 h, the PL intensity and width of TJU-41 and TJU-42 were well retained, superior to the conventional organic–inorganic lead halide perovskites. …”
Section: Resultsmentioning
confidence: 96%
“…The broadband emission from TJU-41 and TJU-42 is highly stable over the chemical treatments in aqueous conditions (pH = 3–11) as well as polar organic solvents (Figure f,g). After incubation in these solutions for 48 h, the PL intensity and width of TJU-41 and TJU-42 were well retained, superior to the conventional organic–inorganic lead halide perovskites. …”
Section: Resultsmentioning
confidence: 96%
“…Recently, exciton self-trapping state engineering via Sb 3+ doping has also been implemented in a 0D (DFPD) 2 CsBiI 6 metal halide, showing broadband NIR STE emission centered at $850 nm. 128 The [SbI 6 ] 3À octahedron can act as a new luminescent center and change the band structure of the material from indirect to semi-direct. Moreover, the Sb 3+ dopant can modify the band edges of VB and CB to be less dispersive, contributing to form more localized electronic states that makes the STE emission possible.…”
Section: Self-trapping State Engineeringmentioning
confidence: 99%
“…309 Notably, this NIR detector had obvious photoresponse at zero bias with a responsivity of 0.0016 A W À1 as well as a detectivity of 3.08 Â 10 10 Jones. Recently, Bai et al 128 fabricated a photodetector based on (DFPD) 2 CsBiI 6 :Sb film, showing the highest responsivity at 365 nm. However, slow response speed was demonstrated, which is probably limited by the low charge carrier mobility of the 0D metal halides that is not conducive to photocurrent generation.…”
Section: Photodetectorsmentioning
confidence: 99%
“…Recently, lead-free perovskites, such as double perovskites and low-dimensional perovskites, have attracted great interest in realizing excitation-dependent emission due to several intrinsic advantages including high photoluminescence quantum yields (PLQYs), low-toxicity, and low-cost solution processing. These systems possess unique soft lattices and strong quantum confinement, which endow them with broadband self-trapped exciton (STE) emission. The existence of multiple emission centers, including STEs, ligands, and doping ions, renders them a perfect platform to achieve excitation-dependent emission. For example, Kuang et al reported a zero-dimensional (0D) indium–antimony alloyed halide perovskite, BAPPIn 1.996 Sb 0.004 Cl 10 , which emits bright yellow light and white light with PLQYs of ca. 100 and 44% at 320 and 365 nm excitation, respectively .…”
Section: Introductionmentioning
confidence: 99%